A Seemingly Insignificant Romanian Word and its English Equivalents - Hortensia Pârlog (ELOPE, 2008)
The paper analyses the various semantic and syntactic roles of the word de and the way in which this seemingly insignificant Romanian word is translated into English. De lacks syntactic and semantic autonomy and has developed both connective and non-connective values, which are usually revealed by the lexico-syntactic information offered by the context in which it appears. It is used as a preposition and, by conversion, as a conjunction, and in both cases, it has acquired multiple (sometimes blurred) values, which make its translation into English difficult sometimes. As a preposition, it marks only relations of subordination within a sentence, as a conjunction, it marks mainly relations of subordination between clauses.